Online Grammar Checker for Syntactic Error Detection and Correction in English Writing - Noobutra, Chutinan (LEARN Journal: Language Education and Acquisition Research Network, 2024)
The present study investigates whether or not Thai students’ English writing skills can be improved by using an online grammar checker. First, typical syntactic errors made by undergraduate students majoring in English and English for Careers were examined. Secondly, possible reasons for syntactic errors in English writing in the light of Lado’s (1957) CAH and Corder’s (1967) EA are explored. Thirdly, it is determined if the number of syntactic errors can be reduced when an online grammar checker is used. Sixty participants were selected employing purposive sampling from students majoring in English and English for Careers. Two sets of test papers were used as the research tool, and errors were analysed before and after the use of an online grammar checker. A comparison of errors made in the two phases could then be used to assess the effectiveness of the online grammar checker. Spelling errors were found to be the most common errors in the present study. The next three most common errors involved capitalisation, verb forms and fragments. All of the students’ errors were caused by L1 transfer, and are referred to as interlingual errors. The findings support the notion that interlingual errors, as predicted by Lado’s (1957) CAH, are the predominant cause of inaccuracies. Meanwhile, English for Careers students made fewer syntactic errors in Phase 2 after learning how to use an online grammar checker to identify and correct syntactic errors, whereas those majoring in English made more errors overall.